ค่าการจราจรสำหรับการวางแผนและออกแบบทางหลวงแผ่นดินในประเทศไทย - เสาวภา มณีเย็น (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The planning and design of highways requires the adjustment of daily traffic volume to be a design hourly volume using design hourly volume factor (K- factor), Daily Factor, and monthly seasonal factor. The design hourly volume factor is unique for particular highways and areas. This study presents the in-depth analyses on the design hourly volume factor and the seasonal factors in Thailand. The data came from 70 Department of Highways permanent traffic count stations, in which the data had continuously collected for 9 years during 2002-2010. The distribution of these hourly traffic volumes were obtained from data which have had complete traffic data. The analyses yielded appropriate hourly conversion factors, namely 30th highest volume, 100th highest volume, daily factor, monthly factor or any value suggested from the field data. The variations of these design hourly volume factors (K- factor) and seasonal factor were classified by regions, and classes of highways using descriptive statistics and Hierarchical Cluster Analysis. The conclusion indicates that the design hourly volume (DHVK100) and the design hourly volume factor (K100) classified by classes of highways in Thailand give the lowest absolute error of the design hour volume and seasonal factors of road sections from different counting methods give the similar absolute error of ADT. These traffic parameters can be appropriately used to estimate future design hourly volumes in Thailand.